Oral medicine, oral pathology and coronavirus (2019-nCoV) - Hercílio Martelli-Júnior; Renato Assis Machado; Daniella R. Barbosa Martelli; Ricardo Della Coletta (Universidade Estadual de Campinas, 2020)
In late December 2019, a cluster of unexplained pneumonia cases was diagnosed in Wuhan, China, and few days later, the causative agent of this mysterious pneumonia was identified as a novel coronavirus. This causative virus has been temporarily named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the relevant infected disease has been named as coronavirus disease 2019 (COVID-19) by the World Health Organization respectively. The COVID-19 epidemic is spreading in China and all over the world now...